Numerical study of flow characteristics around confined cylinder using openFOAM - Mathupriya P.; Chan L.; Hasini H.; Ooi A. (Science Publishing Corporation Inc, 2023)
The numerical study of the flow over a two-dimensional cylinder which is symmetrically confined in a plane channel is presented to study the characteristics of vortex shedding. The numerical model has been established using direct numerical simulation (DNS) based on the open source computational fluid dynamics (CFD) code named OpenFOAM. In the present study, the flow fields have been computed at blockage ratio, ? of 0.5 and at Reynolds number, Re of 200 and 300. Two-dimensional simulations investigated on the effects of Reynolds number based on the vortex formation and shedding frequency. It was observed that the presence of two distinct shedding frequencies appear at higher Reynolds number due to the confinement effects where there is strong interactions between boundary layer, shear layer and the wake of the cylinder. The range of simulations conducted here has shown to produce results consistent with that available in the open literature. Therefore, OpenFOAM is found to be able to accurately capture the complex physics of the flow. 2018 Authors.